Repressing The Fanatism In Madurese Society - Achmad Faidi; Achmad Fauzi; Dimas Danar Septiadi (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2021)
The strong fanaticism and sensitivity of the Madurese society to issues of religious diversities, beliefs or differences in understanding and socio-religious organizations in Madura, make it prone to conflict in the community, such as the Shiite conflict that has occurred in Sampang District, and the difficulty of building worship places for some minority group. The hegemony of a particular religion or religious understanding is the most dominant in the midst of Madurese society, requires the right way to foster attitudes and understanding of the values of tolerance and diversity. This article describes the importance of building public legal awareness through legal culture strengthening in society. The historical normative approach is as the main foundation, such as; the conception of tolerance in religious texts (al-Qur'an and al-hadith), in the Medina Charter, the conception of human rights in the Cairo Declaration, in the Universal Declaration of Human Rights (UDHR), in the 1945 Constitution of Republic of Indonesia as well as several other laws governing religious tolerance and human rights in Indonesia.This article concludes that it is considered important to strengthen the legal culture in society, in order to build public legal awareness and to maximize the function of several existing legal products; especially regarding to the building of tolerance in religions and beliefs that prevail in Indonesia, considering that building the public legal awareness is not enough only being built by the legal substance and legal structure. Strengthening the legal culture can be built through a variety of massive socialization instruments through public spaces, both in academic areas, such as universities and other social institutions.(Kuatnya fanatisme dan sensitifitas masyarakat madura terhadap isu-isu perbedaan agama, keyakinan atau perbedaan paham dan oraganiasi sosial keagamaan di Madura, menyebabkan rawan munculnya konflik di masyarakat, seperti konflik Syi’ah yang pernah terjadi di Kabupaten Sampang, serta susahnya membangun tempat Ibadah bagi sebagian kelompok minoritas. Hegemoni suatu agama atau paham keagamaan tertentu yang paling dominan di tengah-tengah masyarakat Madura, membutuhkan cara yang tepat guna menumbuhkan sikap dan pemahaman tentang nilai-nilai toleransi dan keberagaman. Artikel ini mengurai tentang pentingnya membangun kesadaran hukum masyarakat melalui penguatan legal culture di masyarakat. Pendekatan normative historis sebagai dasar pijakan utama, seperti; konsepsi toleransi dalam teks agama (al-Qur’an dan al-hadits), dalam Piagam Madinah (Madinah Charter), konsepsi HAM dalam Deklarasi Kairo, dalam Universal Declaration of Human Right (UDHR), dalam Undang-undang Dasar Negara Republik Indonesia 1945 serta beberapa Undang-undang lainnya yang mengatur tentang Toleransi beragama dan HAM di Indonesia. Artikel ini berkesimpulah bahwa dipandang penting menguatkan legal culture di masyarakat, dalam rangka membangun kesadaran hukum masyarakat dan memaksimalkan fungsi beberapa produk hukum yang ada, khususnya tentang membangun toleransi beragama dan berkeyakinan yang berlaku di Indonesia, menginat menumbuhkan kesadaran hukum masyarakat tidak cukup hanya dibangun oleh unsur legal substance dan legal structure. Penguatan legal culture dapat dibangun melalui berbagai instrument sosialiasi yang massif melalui ruang-ruang publik, baik dilingkup akedemik, sepert perguruan tinggi maupun lembaga-lembanga social kemasyarakatan lainnya)